Investigating expressed emotion in individuals at‐risk of developing psychosis and their families over 12 months. (22nd February 2021) - Izon, Emma; Berry, Katherine; Wearden, Alison; Carter, Lesley‐Anne; Law, Heather; French, Paul
Abstract: High levels of expressed emotion (EE) are present in families of individuals with an at‐risk mental state (ARMS) of psychosis and can negatively impact on service users' functioning and symptoms, as well as relatives' psychological wellbeing. Objectives: This is the first longitudinal study to assess EE from the family/carers' perspective, as well as the service users' perceptions of the family/carers' EE. We explored the effects of EE on transition risk and outcomes of depression, worry, and anxiety. Methods: Questionnaires were completed by 70 ARMS individuals and 70 family/carers at three time points: baseline, 6 and 12 months. All participants completed measures of anxiety, depression, and worry, plus a version of the Family Questionnaire to assess EE. Results: EE scores reduced over time for both service users and family/carers. High EE perceived by service users at 6 months was associated with higher transition to psychosis at 12 months. High‐EE levels at baseline were associated with higher levels of service user depression and family/carer anxiety at 12 months. Higher family/carer total EE scores were associated with less contact with the service user and higher levels of worry. Conclusions: Novel implications suggest that interventions to reduce high EE in families of people with ARMS would benefit service users by protecting them from higher levels of depression and transition to psychosis. Reducing high‐EE attitudes would also benefit the family/carers by reducing levels of anxiety and worry. Family interventions focussing on multiple perceptions of the home environment could help to direct services and prevent negative psychological outcomes for all family members.